(untitled) (Revista Contexto & Educação, 2025)
Using commercial films in the classroom is a didactic strategy to address and reflect on various themes related to Science. The present qualitative study in education aimed to analyze the potential of the film Tropical Dreams as a trigger for discussions about Health Education (HE) and scientific denialism, with preservice Biology teachers. Methodologically, the research was based on microgenetic analysis, and the subjects were undergraduate students in Biology from a Higher Education Institution (HEI). The empirical data emerged from the analysis of post-film discussions and the students’ Training Diaries. The discussion of the results is anchored in the Historical-Cultural approach proposed by Vygotsky. This study uses the metaphor of winds to highlight the didactic role of the film in the classroom, the meanings, and points of reflection in the debate on HE, scientific denialism, and Scientific Literacy. We conclude that, when using films in teaching, the intentional action of the mediating teacher is essential, as they play a central role in guiding discussions and developing the critical positions of preservice teachers regarding the social context in which they are inserted, in addition to contributing to the construction of the subjects’ scientific knowledge.